2011
DOI: 10.2514/1.j050815
|View full text |Cite
|
Sign up to set email alerts
|

High-Temperature Performance of Actively Cooled Vapor Phase Strengthened Nickel-Based Thermostructural Panels

Abstract: Actively cooled thermostructural panels for use in emerging hypersonic flight systems require advanced materials able to support substantial loads at elevated temperatures. Identifying formable structural materials with strength, toughness, and oxidation resistance is a major challenge in this advancing technology. Geometrical optimization of thermostructural panels for scramjet applications minimizing mass with appropriate mechanical strength and cooling capacity combinations often requires submillimeter wall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2013
2013
2014
2014

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 16 publications
0
1
0
Order By: Relevance
“…In these cases, an additional homogenization step results in a uniform Ni-Al alloy 109,110 or a desired twophase c/c9 microstructure with the corresponding high temperature mechanical stability. 111,112 Conversion of LIGA Ni MEMS components to a Ni-rich two-phase (c-c9) superalloy microstructure via pack aluminization has recently been explored by Burns et al 113 The aluminized components showed significantly improved microstructural stability. Furthermore, the trimodal distribution of c9-precipitates resulted in marked improvements in both room and elevated temperature strength.…”
Section: Vapor Phase Aluminization Of Liga Ni Structuresmentioning
confidence: 99%
“…In these cases, an additional homogenization step results in a uniform Ni-Al alloy 109,110 or a desired twophase c/c9 microstructure with the corresponding high temperature mechanical stability. 111,112 Conversion of LIGA Ni MEMS components to a Ni-rich two-phase (c-c9) superalloy microstructure via pack aluminization has recently been explored by Burns et al 113 The aluminized components showed significantly improved microstructural stability. Furthermore, the trimodal distribution of c9-precipitates resulted in marked improvements in both room and elevated temperature strength.…”
Section: Vapor Phase Aluminization Of Liga Ni Structuresmentioning
confidence: 99%